A ferrous sulfide passivation deodorant and its preparation process
Through the oxidation and passivation of ferrous sulfide passivation deodorant, the problems of ferrous sulfide spontaneous combustion and environmental pollution in crude oil processing are solved, efficient decontamination and corrosion resistance are achieved, and the safety of equipment and environment is ensured. .
Patent Information
- Application Number
- CN202411357898.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-27
AI Technical Summary
During crude oil processing, ferrous sulfide (FeS) is easily enriched and causes equipment to ignite spontaneously, causing fire accidents. At the same time, traditional steam purge methods pollute the environment and affect maintenance safety and health.
A ferrous sulfide passivation deodorant is adopted, including sodium percarbonate, sodium bicarbonate, diethyltriamine pentaacetic acid, nonylphenol polyoxyethylene ether, cocoa acid propyl betaine, coconut oil alkyl diethyl Ethanamide, benzotriazole, chitosan, biocatalyst and sodium silicate prevent spontaneous combustion and improve cleaning efficiency through oxidation and passivation.
Through multiple oxidation and passivation effects, this deodorant efficiently removes stains and deodorizes, prevents spontaneous ignition of ferrous sulfide, reduces environmental pollution, improves equipment cleaning efficiency, and ensures maintenance safety.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of passivation deodorants, and more specifically, to a ferrous sulfide passivation deodorant and a preparation process thereof. Background Art
[0002] In the crude oil processing process, the sulfur-making unit belongs to the terminal unit of the oil refining, and its raw materials contain a large amount of hydrogen sulfide and ammonia nitrogen substances. These substances will generate ferrous sulfide (FeS) when they come into contact with the equipment. This substance is easy to be enriched in the tower packing, tower tray or the bottom of the equipment, and is wrapped by impurities in the viscous sewage, and is not easily carried away by the fluid. When the oil refining unit is shut down for maintenance, even after steam purging and water washing, a large amount of ferrous sulfide will still remain in the equipment. After the equipment is turned on, oxygen in the air enters the interior of the equipment and reacts violently with FeS, releasing a large amount of heat, thereby causing spontaneous combustion, which may lead to fire accidents. In addition, FeS spontaneous combustion produces Fe2O3, which will block pipelines and valves, and the generated SO2 is highly irritating, toxic and polluting.
[0003] As crude oil quality deteriorates and deep processing equipment increases, the sulfur-containing wastewater, hydrogen sulfide and ammonia nitrogen content generated during the refining process continue to increase, and the environmental pollution problem caused by equipment shutdown and maintenance is becoming increasingly serious. The traditional steam purge method will directly discharge steam, hydrogen sulfide and ammonia nitrogen into the atmosphere, which not only pollutes the environment but also threatens the health of maintenance personnel. Therefore, it is imperative to develop a ferrous sulfide passivation deodorant that improves the efficiency of equipment and pipeline cleaning and deodorization, and prevents FeS spontaneous combustion and odorous gas pollution. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a ferrous sulfide passivation deodorant and a preparation process thereof.
[0005] A ferrous sulfide passivation deodorant, comprising the following raw materials in percentage by mass:
[0006] Sodium percarbonate 0.8%–1.0%, sodium bicarbonate 0.5%–0.7%, diethylenetriaminepentaacetic acid 0.3%–0.4%, nonylphenol polyoxyethylene ether 0.2%–0.3%, cocamidopropyl betaine 0.3%–0.35%, coconut oil alkyl diethanolamide 0.4%–0.5%, benzotriazole 0.1%–0.15%, chitosan 0.1%–0.15%, biocatalyst 0.05%–0.08%, sodium silicate 0.4%–0.6%, sodium gluconate 0.3%–0.5%, and water as the balance.
[0007] A ferrous sulfide passivation deodorant, comprising the following preferred raw materials in percentage by mass:
[0008] Sodium percarbonate 0.9%, sodium bicarbonate 0.6%, diethylenetriaminepentaacetic acid 0.35%, nonylphenol polyoxyethylene ether 0.25%, cocoamidopropyl betaine 0.32%, coconut oil alkyl diethanolamide 0.45%, benzotriazole 0.12%, chitosan 0.12%, biocatalyst 0.07%, sodium silicate 0.5%, sodium gluconate 0.4%, balance water.
[0009] A ferrous sulfide passivation deodorant, comprising the following preferred raw materials in percentage by mass:
[0010] Sodium percarbonate 0.8%, sodium bicarbonate 0.5%, diethylenetriaminepentaacetic acid 0.3%, nonylphenol polyoxyethylene ether 0.2%, cocoamidopropyl betaine 0.3%, coconut oil alkyl diethanolamide 0.4%, benzotriazole 0.1%, chitosan 0.1%, biocatalyst 0.05%, sodium silicate 0.4%, sodium gluconate 0.3%, balance water.
[0011] A ferrous sulfide passivation deodorant, comprising the following preferred raw materials in percentage by mass:
[0012] Sodium percarbonate 1.0%, sodium bicarbonate 0.7%, diethylenetriamine pentaacetic acid 0.4%, nonylphenol polyoxyethylene ether 0.3%, cocoamidopropyl betaine 0.35%, coconut oil alkyl diethanolamide 0.5%, benzotriazole 0.15%, chitosan 0.15%, biocatalyst 0.08%, sodium silicate 0.6%, sodium gluconate 0.5%, balance water.
[0013] Preferably, the biocatalyst is one or more of urease or sulfatase.
[0014] A preparation process of a ferrous sulfide passivation deodorant comprises the following steps:
[0015] S1: Preparation and Mixing;
[0016] Pour water into the mixing container and start the stirring device to ensure uniform mixing of the solution;
[0017] S2: Add surfactant and corrosion inhibitor;
[0018] Add nonylphenol polyoxyethylene ether and benzotriazole to the water in the stirring container in sequence, and stir until they are completely dissolved;
[0019] Then add the cocamidopropyl betaine and coconut alkyl diethanolamide and continue stirring to ensure complete dissolution and even dispersion.
[0020] S3: introduction of chelating agents and biocatalysts;
[0021] Add diethylenetriaminepentaacetic acid and sodium gluconate to the mixture and stir until dissolved;
[0022] Add chitosan and continue stirring to ensure dissolution and uniform dispersion;
[0023] Then add the biocatalyst and stir until well mixed;
[0024] S4: adding passivation and protection components;
[0025] Add sodium silicate and stir to dissolve, making sure it is evenly mixed;
[0026] Finally, add the sodium percarbonate and sodium bicarbonate, continuing to stir to ensure that all ingredients are fully dissolved and evenly distributed;
[0027] S5: end stirring;
[0028] Keep stirring to ensure all ingredients are fully dissolved and evenly mixed;
[0029] S6: Packaging and storage;
[0030] The prepared ferrous sulfide passivation deodorant solution is filtered to remove undissolved particles, and the filtered solution is placed in a suitable plastic or stainless steel container and sealed for storage, avoiding direct sunlight and high temperature environment.
[0031] Preferably, in step S2, nonylphenol polyoxyethylene ether and benzotriazole are added to the water in the stirring container in sequence, the stirring time is 30-60 minutes, the stirring temperature is 25-40° C., and the stirring is carried out until they are completely dissolved.
[0032] Preferably, in step S3, diethylenetriaminepentaacetic acid and sodium gluconate are added to the mixed solution, stirred for 30-60 min, at a temperature of 25-35° C., and stirred until completely dissolved.
[0033] Preferably, in step S4, sodium silicate is added, the stirring time is 30-50 min, the stirring temperature is 25-30° C., and after stirring and dissolving, ensure uniform mixing.
[0034] Preferably: in step S5, the stirring time is 3-10 min, and the stirring temperature is 25-35°C.
[0035] The beneficial effects of the present invention are as follows: the ferrous sulfide passivation deodorant proposed by the present invention uses sodium percarbonate as a main oxidant, and the sodium percarbonate decomposes in water to generate hydrogen peroxide and sodium carbonate. The hydrogen peroxide is a strong oxidant and can oxidize ferrous sulfide (FeS), passivate its reaction activity, and prevent spontaneous combustion.
[0036] Sodium bicarbonate acts as a buffer to stabilize the pH of the solution, prevent excessive decomposition of hydrogen peroxide, and neutralize acidic substances to prevent corrosion.
[0037] As a chelating agent, DTPA can chelate heavy metal ions such as iron and copper in water, preventing these metal ions from catalyzing the decomposition of hydrogen peroxide and reducing metal corrosion on the surface of equipment.
[0038] As a highly efficient nonionic surfactant, nonylphenol polyoxyethylene ether can reduce the surface tension of water and improve cleaning ability, especially for cleaning oil and organic matter.
[0039] Cocoamidopropyl Betaine is a mild amphoteric surfactant with good detergency and foam stability.
[0040] Coconut oil alkyl diethanolamide is a nonionic surfactant with good detergency and delicate foam, which enhances the cleaning effect.
[0041] Benzotriazole is a highly effective metal corrosion inhibitor, especially used for the protection of copper and its alloys.
[0042] Chitosan is a natural polymer adsorbent that can effectively adsorb heavy metal ions and organic pollutants.
[0043] Urease or sulfatase, as biological catalysts, can effectively decompose urea or organic sulfides and enhance the deodorization effect.
[0044] Sodium silicate enhances oxidation and passivation effects and provides a protective film against metal corrosion.
[0045] Sodium gluconate acts as a chelating agent and dispersant to prevent scale formation and improve cleaning results.
[0046] Sodium percarbonate and sodium silicate: Sodium percarbonate provides oxidation, and sodium silicate forms a protective layer, with dual anti-corrosion and passivation effects.
[0047] Sodium bicarbonate and sodium percarbonate: Sodium bicarbonate acts as a buffer to stabilize the decomposition of sodium percarbonate and improve the overall oxidation effect.
[0048] DTPA and sodium gluconate: The two work together to provide a strong chelation effect to prevent scale formation and corrosion caused by metal ions.
[0049] Nonylphenol polyoxyethylene ether, cocoamidopropyl betaine, coconut oil alkyl diethanolamide: form a multi-surfactant system to enhance cleaning and decontamination capabilities.
[0050] Benzotriazole and sodium silicate: together form a highly effective anti-corrosion protective layer, doubly protecting against metal corrosion.
[0051] Chitosan and specific enzymes (urease or sulfatase): Chitosan absorbs pollutants, and enzymes decompose organic matter, improving deodorization and purification effects.
[0052] The ferrous sulfide passivation deodorant proposed by the invention has multiple oxidation and passivation effects, can remove dirt and deodorize with high efficiency, has comprehensive anti-corrosion and chelating protection capabilities, and can reduce pollution to the environment. DETAILED DESCRIPTION
[0053] The subject matter described herein will now be discussed with reference to example embodiments. It should be understood that the discussion of these embodiments is only to enable those skilled in the art to better understand and implement the subject matter described herein, and the functions and arrangements of the elements discussed may be changed without departing from the scope of protection of the contents of this specification. Each example may omit, replace or add various processes or components as needed. In addition, the features described relative to some examples may also be combined in other examples.
[0054] Example 1
[0055] In the embodiment, a ferrous sulfide passivation deodorant is proposed, comprising the following raw materials in percentage by mass:
[0056] Sodium percarbonate 0.9%, sodium bicarbonate 0.6%, diethylenetriaminepentaacetic acid 0.35%, nonylphenol polyoxyethylene ether 0.25%, cocoamidopropyl betaine 0.32%, coconut oil alkyl diethanolamide 0.45%, benzotriazole 0.12%, chitosan 0.12%, biocatalyst 0.07%, sodium silicate 0.5%, sodium gluconate 0.4%, balance water.
[0057] The biocatalyst is urease.
[0058] The preparation process of the ferrous sulfide passivation deodorant in this embodiment comprises the following steps:
[0059] S1: Preparation and Mixing;
[0060] Pour water into the mixing container and start the stirring device to ensure uniform mixing of the solution;
[0061] S2: Add surfactant and corrosion inhibitor;
[0062] Add nonylphenol polyoxyethylene ether and benzotriazole to the water in the stirring container in sequence, stirring for 45 minutes at a stirring temperature of 30°C until completely dissolved;
[0063] Then add the cocamidopropyl betaine and coconut alkyl diethanolamide and continue stirring to ensure complete dissolution and even dispersion.
[0064] S3: introduction of chelating agents and biocatalysts;
[0065] Add diethylenetriaminepentaacetic acid and sodium gluconate to the mixture, stir for 45 min at 29°C until dissolved;
[0066] Add chitosan and continue stirring to ensure dissolution and uniform dispersion;
[0067] Then add urease and stir until well mixed;
[0068] S4: adding passivation and protection components;
[0069] Add sodium silicate and stir to dissolve. Stir for 40 minutes at 27°C to ensure uniform mixing.
[0070] Finally, add the sodium percarbonate and sodium bicarbonate, continuing to stir to ensure that all ingredients are fully dissolved and evenly distributed;
[0071] S5: end stirring;
[0072] Continue stirring for 6 minutes at a temperature of 30°C to ensure that all ingredients are completely dissolved and evenly mixed;
[0073] S6: Packaging and storage;
[0074] The prepared ferrous sulfide passivation deodorant solution is filtered to remove undissolved particles, and the filtered solution is placed in a suitable plastic or stainless steel container and sealed for storage, avoiding direct sunlight and high temperature environment.
[0075] Example 2
[0076] In the embodiment, a ferrous sulfide passivation deodorant is proposed, comprising the following raw materials in percentage by mass:
[0077] Sodium percarbonate 0.8%, sodium bicarbonate 0.5%, diethylenetriaminepentaacetic acid 0.3%, nonylphenol polyoxyethylene ether 0.2%, cocoamidopropyl betaine 0.3%, coconut oil alkyl diethanolamide 0.4%, benzotriazole 0.1%, chitosan 0.1%, biocatalyst 0.05%, sodium silicate 0.4%, sodium gluconate 0.3%, balance water.
[0078] The biocatalyst is sulfatase.
[0079] The preparation process of the ferrous sulfide passivation deodorant in this embodiment comprises the following steps:
[0080] S1: Preparation and Mixing;
[0081] Pour water into the mixing container and start the stirring device to ensure uniform mixing of the solution;
[0082] S2: Add surfactant and corrosion inhibitor;
[0083] Add nonylphenol polyoxyethylene ether and benzotriazole to the water in the stirring container in sequence, stirring for 30 minutes at a stirring temperature of 40°C until they are completely dissolved;
[0084] Then add the cocamidopropyl betaine and coconut alkyl diethanolamide and continue stirring to ensure complete dissolution and even dispersion.
[0085] S3: introduction of chelating agents and biocatalysts;
[0086] Add diethylenetriaminepentaacetic acid and sodium gluconate to the mixture, stir for 30 min at 35°C until dissolved;
[0087] Add chitosan and continue stirring to ensure dissolution and uniform dispersion;
[0088] Then add sulfatase and stir until well mixed;
[0089] S4: adding passivation and protection components;
[0090] Add sodium silicate and stir until dissolved. Stir for 30 minutes at a temperature of 30°C to ensure uniform mixing.
[0091] Finally, add the sodium percarbonate and sodium bicarbonate, continuing to stir to ensure that all ingredients are fully dissolved and evenly distributed;
[0092] S5: end stirring;
[0093] Continue stirring for 3 minutes at a temperature of 35°C to ensure that all ingredients are completely dissolved and evenly mixed;
[0094] S6: Packaging and storage;
[0095] The prepared ferrous sulfide passivation deodorant solution is filtered to remove undissolved particles, and the filtered solution is placed in a suitable plastic or stainless steel container and sealed for storage, avoiding direct sunlight and high temperature environment.
[0096] Example 3
[0097] In the embodiment, a ferrous sulfide passivation deodorant is proposed, comprising the following raw materials in percentage by mass:
[0098] Sodium percarbonate 1.0%, sodium bicarbonate 0.7%, diethylenetriamine pentaacetic acid 0.4%, nonylphenol polyoxyethylene ether 0.3%, cocoamidopropyl betaine 0.35%, coconut oil alkyl diethanolamide 0.5%, benzotriazole 0.15%, chitosan 0.15%, biocatalyst 0.08%, sodium silicate 0.6%, sodium gluconate 0.5%, balance water.
[0099] The biocatalysts are urease and sulfatase.
[0100] The preparation process of the ferrous sulfide passivation deodorant in this embodiment comprises the following steps:
[0101] S1: Preparation and Mixing;
[0102] Pour water into the mixing container and start the stirring device to ensure uniform mixing of the solution;
[0103] S2: Add surfactant and corrosion inhibitor;
[0104] Add nonylphenol polyoxyethylene ether and benzotriazole to the water in the stirring container in sequence, stirring for 60 minutes at a stirring temperature of 25°C until completely dissolved;
[0105] Then add the cocamidopropyl betaine and coconut alkyl diethanolamide and continue stirring to ensure complete dissolution and even dispersion.
[0106] S3: introduction of chelating agents and biocatalysts;
[0107] Add diethylenetriaminepentaacetic acid and sodium gluconate to the mixture, stir for 60 min at 25°C until dissolved;
[0108] Add chitosan and continue stirring to ensure dissolution and uniform dispersion;
[0109] Then add urease and sulfatase and stir until well mixed;
[0110] S4: adding passivation and protection components;
[0111] Add sodium silicate and stir until dissolved. Stir for 50 minutes at a temperature of 25°C to ensure uniform mixing.
[0112] Finally, add the sodium percarbonate and sodium bicarbonate, continuing to stir to ensure that all ingredients are fully dissolved and evenly distributed;
[0113] S5: end stirring;
[0114] Continue stirring for 10 minutes at a temperature of 25°C to ensure that all ingredients are completely dissolved and evenly mixed;
[0115] S6: Packaging and storage;
[0116] Filter the prepared ferrous sulfide passivation deodorant solution to remove undissolved particles, and store the filtered solution in a suitable plastic or stainless steel container in a sealed container, away from direct sunlight and high temperature environment.
[0117] Example 4
[0118] This example is used to verify the dual anticorrosion and passivation effects of sodium percarbonate and sodium silicate.
[0119] 1. Experimental principle.
[0120] Sodium percarbonate decomposes in water to produce hydrogen peroxide and sodium carbonate. Hydrogen peroxide is a strong oxidant that can oxidize ferrous sulfide to produce stable ferrous sulfate, thereby passivating its reactivity and preventing spontaneous combustion. Sodium silicate hydrolyzes in water to produce silicic acid and sodium hydroxide. Silicic acid further condenses on the metal surface to form an insoluble silicon dioxide protective film, thereby forming a physical protective layer to prevent further corrosion.
[0121] Chemical reaction:
[0122]
[0123] 2. Experimental steps.
[0124] Preparation before the experiment:
[0125] Beaker, measuring cylinder, pipette, magnetic stirrer, UV spectrophotometer, ICP-OES (inductively coupled plasma optical emission spectrometer), ferrous sulfide, sodium percarbonate, sodium silicate.
[0126] Experimental steps:
[0127] 1) Prepare the solution.
[0128] Weigh a certain amount of sodium percarbonate (0.5 g) and sodium silicate (0.5 g) and dissolve them in 100 ml of deionized water respectively to prepare sodium percarbonate solution and sodium silicate solution.
[0129] FeS samples (1.0 g) were placed in two sets of 250 ml beakers, labeled as “control group” and “experimental group” respectively.
[0130] 2) Add sodium percarbonate.
[0131] Add sodium percarbonate solution into the "experimental group" beaker and place it on a magnetic stirrer for stirring.
[0132] Add the same volume of deionized water (without sodium percarbonate) to the "control" and stir.
[0133] 3) Add sodium silicate.
[0134] After 10 minutes, add an equal amount of sodium silicate solution to the "experimental group".
[0135] At the same time, an equal amount of deionized water (without sodium silicate) was added to the “control group”.
[0136] 4) Observe the reaction phenomenon.
[0137] Continue stirring and observe the reaction phenomena: including the change in solution color and the precipitation produced during the reaction.
[0138] Record the changes every 10 minutes.
[0139] 5) Sampling and testing.
[0140] Every 10 minutes, 1 ml of sample was taken with a pipette, placed in a centrifuge tube, and marked with the time (0 min, 10 min, 20 min, 30 min).
[0141] The Fe content in the sample was detected by UV spectrophotometer. 2+ Observe and record the concentration changes.
[0142] The residual FeS content was determined by adding 0.1 mol / L HCl to titrate the sample.
[0143] 6) End point analysis.
[0144] The reaction was terminated after 30 minutes, and the amount of FeSO4 generated in the solution and the amount of Fe in the solution were determined by ICP-OES. 2+ Adjust the amount and calculate.
[0145] Observe and record the SiO2 protective layer formed on the metal surface.
[0146] 3. Experimental results.
[0147] As shown in the following table:
[0148]
[0149] 4. Results and conclusions
[0150] Result analysis:
[0151] After sodium percarbonate was added to the experimental group, the remaining amount of FeS decreased significantly and a large amount of FeSO4 was generated, indicating that the hydrogen peroxide in sodium percarbonate effectively oxidized FeS into FeSO4.
[0152] The addition of sodium silicate allowed the experimental group to form a layer of SiO2 protective film on the metal surface, further protecting the metal from corrosion.
[0153] In the control group, since no sodium percarbonate and sodium silicate were added, the residual amount of FeS did not change much and the amount of FeSO4 generated was also small, indicating that there was no obvious oxidation and protective layer formation effect.
[0154] in conclusion:
[0155] The experiment verified the effectiveness of sodium percarbonate as the main oxidant. The hydrogen peroxide generated by the decomposition of sodium percarbonate in water can effectively oxidize ferrous sulfide (FeS) to generate stable ferrous sulfate (FeSO4), passivating its reaction activity and preventing spontaneous combustion.
[0156] Sodium silicate can form a SiO2 protective layer on the metal surface, providing physical isolation and further preventing metal surface corrosion.
[0157] The combination of sodium percarbonate and sodium silicate provides both oxidation and protective layer, doubly protecting the metal surface and verifying the dual anti-corrosion and passivation effects.
[0158] Example 5
[0159] This example is used to verify that the synergistic effect of sodium bicarbonate and sodium percarbonate improves the overall oxidation effect.
[0160] 1. Experimental Principle
[0161] As a buffer, sodium bicarbonate can stabilize the hydrogen peroxide generated by the decomposition of sodium percarbonate, improve the stability of hydrogen peroxide in the solution, and increase its oxidative efficiency. The hydrogen peroxide generated by the decomposition of sodium percarbonate is a strong oxidant that can oxidize many organic and inorganic substances. Through the buffering effect of sodium bicarbonate, the pH value of the solution can be maintained, so that the decomposition rate of hydrogen peroxide is kept in the optimal range, achieving a higher oxidation effect.
[0162] Decomposition reaction:
[0163]
[0164] Oxidation reaction:
[0165]
[0166] 2. Experimental steps.
[0167] Preparation before the experiment:
[0168] Beaker, measuring cylinder, pipette, magnetic stirrer, UV spectrophotometer, pH meter, ferrous sulfide (FeS) sample, sodium percarbonate, sodium bicarbonate.
[0169] Experimental steps:
[0170] 1) Prepare the solution.
[0171] Take two groups of 250ml beakers and prepare 100ml solution in each group. Divide them into experimental group and control group.
[0172] Experimental group: Weigh 0.5 g of sodium percarbonate and 0.5 g of sodium bicarbonate and dissolve them in 100 ml of deionized water respectively.
[0173] Control group: weigh 0.5 g of sodium percarbonate and dissolve it in 100 ml of deionized water (without adding sodium bicarbonate).
[0174] 2) Add FeS sample.
[0175] Add 1.0 g of crushed ferrous sulfide (FeS) to each of the two beakers, record the initial pH value, and then place them on a magnetic stirrer and start stirring.
[0176] 3) The reaction starts.
[0177] The initial reaction time was recorded and changes in the reaction solution were observed, including bubbling (indicating decomposition of hydrogen peroxide) and changes in solution color.
[0178] 4) Take samples at regular intervals.
[0179] Every 10 minutes, 1 ml of sample was taken with a pipette, placed in centrifuge tubes, marked with time (0 min, 10 min, 20 min, 30 min), and the pH value was measured.
[0180] The Fe content in the sample was detected by UV spectrophotometer. 2+ The content changes and is recorded to determine the remaining reaction volume.
[0181] 5) End point detection and processing:
[0182] The reaction was terminated after 30 minutes. A 1 ml sample was taken with a pipette, and 0.1 mol / L HCl was added for titration. The amount of FeSO4 generated was determined using a UV spectrophotometer, and the FeS conversion rate was recorded and calculated.
[0183] 3. Experimental results.
[0184] As shown in the following table:
[0185]
[0186] 4. Results analysis and conclusion.
[0187] pH stability: After adding sodium bicarbonate, the pH value of the experimental group was relatively stable, maintained between 8.7 and 9.0, while the pH value of the control group gradually decreased and finally dropped to 5.5. Sodium bicarbonate effectively stabilized the pH value of the solution.
[0188] Fe 2+ Concentration changes: Fe in the experimental group 2+ The concentration was significantly higher than that of the control group, indicating that under stable pH conditions, hydrogen peroxide has a stronger oxidizing ability and produces more FeSO4.
[0189] FeS Residual Amount: The FeS residual amount in the experimental group was significantly lower than that in the control group. After 30 minutes, only 15% remained in the experimental group, while 40% remained in the control group. This further verifies the buffering effect of sodium bicarbonate and improves the overall oxidation effect of sodium percarbonate.
[0190] in conclusion:
[0191] This experiment verified that sodium bicarbonate, as a buffer, can effectively stabilize the hydrogen peroxide generated by the decomposition of sodium percarbonate, improve the stability of hydrogen peroxide, and enhance its oxidative efficiency.
[0192] Experiments show that under stable pH conditions, the oxidation effect of sodium percarbonate is significantly enhanced, FeS is more effectively oxidized to FeSO4, and the risk of spontaneous combustion is reduced.
[0193] Through the synergistic effect of sodium bicarbonate and sodium percarbonate, the problem of rapid decomposition of hydrogen peroxide under acidic conditions is solved, the overall oxidation efficiency is improved, and a reliable basis is provided for the stability of oxidants in industrial applications.
[0194] Example 6
[0195] This example is used to verify that DTPA and sodium gluconate work synergistically to prevent scale formation and corrosion caused by metal ions.
[0196] 1. Experimental principle.
[0197] Diethylenetriaminepentaacetic acid (DTPA) and sodium gluconate are effective chelating agents that bind metal ions such as calcium (Ca 2+ ), magnesium (Mg 2+ ) and iron (Fe 2+ ), preventing these ions from reacting with carbonate ions (CO3 2- ) or hydroxide ion (OH - ) combine to form insoluble scale and reduce the corrosion reaction catalyzed by metal ions. DTPA and sodium gluconate can work together to form a stable chelate, improve chelation efficiency, prevent scale formation and reduce metal corrosion.
[0198] Chelation reaction:
[0199]
[0200] 2. Experimental steps.
[0201] Preparation before the experiment:
[0202] Beaker, measuring cylinder, pipette, magnetic stirrer, UV spectrophotometer, pH meter, ICP-OES (inductively coupled plasma optical emission spectrometer), calcium / magnesium hydroxide (Ca(OH)2, Mg(OH)2), iron chloride (FeCl3), diethylenetriaminepentaacetic acid (DTPA), sodium gluconate.
[0203] Experimental steps:
[0204] 1) Prepare the solution.
[0205] Prepare 100mg / L Ca 2+ and 100mg / L Mg 2+ Mixed solution, 50mg / L Fe 2+ The solutions were placed in two 250ml beakers and divided into an experimental group and a control group.
[0206] Experimental group: 0.5 g DTPA and 0.5 g sodium gluconate were added to two beakers respectively.
[0207] Control group: Use excess deionized water to dissolve the same amount of Ca 2+ Mg 2+ and Fe 2+ Solution.
[0208] 2) Stir to dissolve.
[0209] Place on a magnetic stirrer and stir (300 rpm) to ensure that the solution is evenly mixed and integrated.
[0210] 3) Add sodium carbonate solution.
[0211] Dissolve 0.5 g of sodium carbonate in 50 ml of deionized water and slowly add it to the experimental and control group solutions while maintaining stirring.
[0212] Observe and record changes in the solution, especially the amount of precipitate formed.
[0213] 4) Take samples at regular intervals.
[0214] Every 10 minutes, 1 ml of the sample was taken out with a pipette, placed in centrifuge tubes, and the precipitate was separated by centrifugation.
[0215] The remaining metal ions (Ca 2+ Mg 2+ and Fe 2+ ) content and the mass of the formed precipitate were determined.
[0216] 5) End point detection and processing.
[0217] The reaction was terminated after 30 minutes, the residual ion content was determined (analyzed by ICP-OES), and the formation of precipitates was recorded and analyzed.
[0218] The quality and quantity of the sediment were detected using an ultraviolet spectrophotometer, and the comparative data of the scale removal between the two groups were calculated.
[0219] 3. Experimental results.
[0220] As shown in the following table:
[0221]
[0222] 4. Results analysis and conclusion.
[0223] Chelating capacity: The remaining metal ions (Ca 2+ Mg 2+ and Fe 2+ ) concentrations were significantly higher than those in the control group, indicating that DTPA and sodium gluconate effectively chelated and stabilized these metal ions and prevented the formation of insoluble precipitates.
[0224] Chelation efficiency: The experimental group still had 65 mg / L of Ca after 30 minutes. 2+ , 55 mg / L Mg 2+ and 20 mg / L Fe 2+ , indicating that these metal ions are effectively chelated; while the control group is significantly reduced, indicating that when there is no chelating factor, most of the metal ions participate in the scale formation reaction.
[0225] in conclusion:
[0226] This experiment verified that DTPA and sodium gluconate work synergistically to effectively chelate sulfur-containing alkaline metal ions, preventing them from reacting with sodium carbonate and sodium hydroxide to form precipitation and prevent the formation of scale.
[0227] At the same time, the chelation of metal ions reduces the catalyst of the oxidation reaction, reduces the risk of corrosion, and improves the stability of the system.
[0228] The combination of DTPA and sodium gluconate improves the protection performance of the system, providing an effective solution for corrosion control and water purification in complex industrial processes.
[0229] Example 7
[0230] This example is used to verify the effect of "nonylphenol polyoxyethylene ether, cocamidopropyl betaine, and coconut oil alkyl diethanolamide forming a multi-surfactant system to enhance cleaning and decontamination capabilities".
[0231] 1. Experimental Principle
[0232] By combining nonylphenol polyoxyethylene ether (NP-n), cocamidopropyl betaine (CocamidopropylBetaine) and coconut oil alkyl diethanolamide (Cocamide DEA), a multi-surfactant system is formed in the solution. This system uses the synergistic effect of each component to enhance the ability of interfacial activity, emulsification, dispersion and decontamination. The experiment verifies that the system is significantly improved compared with a single surfactant by measuring the decontamination efficiency and cleaning ability.
[0233] The working principle of surfactants:
[0234] Nonylphenol polyoxyethylene ether (NP-n): nonionic surfactant that reduces surface tension and enhances emulsification effect.
[0235] Cocoamidopropyl Betaine: Amphoteric surfactant that provides mild detergency and stable foaming ability.
[0236] Coconut Oil Alkyl Diethanolamide: Nonionic surfactant that further enhances detergency and foam stability.
[0237] 2. Experimental Procedure
[0238] Preparation before the experiment:
[0239] Beaker, measuring cylinder, pipette, magnetic stirrer, pH meter, chelating agent for determining the decontamination ability, contaminated sample, multiple surfactant ingredients: nonylphenol polyoxyethylene ether (NP-n), cocoamidopropyl betaine, coconut oil alkyl diethanolamide.
[0240] Experimental steps:
[0241] 1) Prepare cleaning solution.
[0242] Four groups of 250ml beakers were prepared, one for the experimental group and three for the control group:
[0243] Experimental group: 0.1 g NP-n, 0.1 g cocoamidopropyl betaine and 0.1 g coconut oil alkyl diethanolamide were added to each group and dissolved in 100 ml deionized water to form a multi-surfactant solution.
[0244] Control group 1: A surfactant solution containing only 0.3 g of NP-n was prepared.
[0245] Control group 2: A surfactant solution containing only 0.3 g of cocamidopropyl betaine was prepared.
[0246] Control group 3: a surfactant solution containing only 0.3 g of coconut oil alkyl diethanolamide was prepared.
[0247] 2) Prepare the contaminated solution.
[0248] A uniformly prepared 100 ml pollution solution was selected, containing pollutants such as heavy metal ions and oil (1 g of the polluted sample was dissolved in 100 ml of deionized water).
[0249] 3) Cleaning test.
[0250] Add the cleaning solution and the contamination solution separately and stir for 5 minutes on a magnetic stirrer.
[0251] Take 10 ml of each solution and add it to the contaminated solution. Continue stirring for 15 minutes. Use a pH meter to monitor the changes in the solution during the process.
[0252] 4) Sampling and testing.
[0253] Use a pipette to take samples at regular intervals (take 1 ml every 5 minutes and record them as 0 min, 5 min, 10 min, and 15 min respectively).
[0254] The filtration was carried out and the heavy metal residue and oil removal rate in the filtrate were measured respectively (using standard decontamination ability reagent for detection).
[0255] 5) End point detection.
[0256] The cleanliness, pH value, and pollutant removal rate of each group of filtrates were recorded, and an ultraviolet spectrophotometer was used to detect the removal efficiency of pollutants in different groups.
[0257] 3. Experimental results.
[0258] As shown in the following table:
[0259]
[0260] 4. Results analysis and conclusion.
[0261] Comprehensive decontamination effect: The residual concentration of pollutants in the experimental group was significantly lower than that in the control groups, indicating that the multi-surfactant system has a higher decontamination ability.
[0262] Increased decontamination efficiency: After 15 minutes, only 100 mg / L of pollutants remained in the experimental group, while 450-500 mg / L of pollutants remained in the control group, significantly illustrating the advantage of synergy.
[0263] Stability and cleaning effect: The pH value of the solution in the experimental group changed little, indicating that the multi-surfactant system has good stability and sustainability during long-term stirring.
[0264] Conclusion: This experiment verified that the multi-surfactant system formed by nonylphenol polyoxyethylene ether, cocoamidopropyl betaine and coconut oil alkyl diethanolamide can significantly enhance the detergency during cleaning and decontamination.
[0265] The synergistic effect of multiple surfactants utilizes the different functional properties of each ingredient to jointly enhance the cleaning and pollutant removal effects of the entire cleaning system.
[0266] The system exhibits excellent stability and high-efficiency decontamination ability, providing a reliable and efficient solution for industrial cleaning and has broad application prospects.
[0267] Example 8
[0268] This example is used to verify that benzotriazole and sodium silicate together form a highly effective anti-corrosion protective layer, which has a dual effect of resisting metal corrosion.
[0269] 1. Experimental principle.
[0270] The anti-corrosion system formed by benzotriazole and sodium silicate can effectively prevent corrosion on metal surfaces. BTA forms a stable adsorption film on the surface of metals (especially copper and its alloys), which plays a chemical passivation role; sodium silicate hydrolyzes on the metal surface to form silicic acid, which further condenses to form an insoluble silicon dioxide film, providing physical isolation. The two work together to form a double anti-corrosion protection, preventing oxygen and corrosive substances from directly contacting the metal surface.
[0271] Chemical passivation reaction of BTA:
[0272]
[0273] Hydrolysis and condensation reaction of sodium silicate:
[0274]
[0275] 2. Experimental steps.
[0276] Preparation before the experiment: beaker, measuring cylinder, pipette, magnetic stirrer, pH meter, UV spectrophotometer, electrochemical workstation, metal sample (copper or iron sheet), benzotriazole, sodium silicate, and corrosive medium.
[0277] Experimental steps:
[0278] 1) Prepare metal samples: Take two copper or iron sheets of the same size and mark them as "experimental group" and "control group" respectively. Use sandpaper to polish the metal surface and clean it with deionized water.
[0279] 2) Prepare the solution.
[0280] Prepare 100 ml of solution in each of two beakers:
[0281] Experimental group: 0.5 g BTA and 0.5 g sodium silicate were added and dissolved in 100 ml deionized water.
[0282] Control group: only 0.5 g of sodium silicate was dissolved in 100 ml of deionized water (without adding BTA).
[0283] 3) Processing of metal samples.
[0284] Soak the copper or iron pieces in the beaker for 30 minutes respectively, while keeping the solution on a magnetic stirrer to ensure that the solution evenly contacts the metal surface.
[0285] 4) Corrosion test.
[0286] The treated metal samples were taken out, rinsed with deionized water and blown dry.
[0287] The two groups of samples were placed in beakers containing 3.5% NaCl solution, the solutions were kept at rest, and the start time was recorded.
[0288] 5) Timed measurement: Use a pH meter to measure the pH change of the solution every hour. Use an electrochemical workstation to perform electrochemical impedance measurement to evaluate the metal corrosion reaction rate. Record the solution color and rust condition.
[0289] 6) End point analysis: After 24 hours, take out the metal sample and use UV spectrophotometer to measure the Cu content in the solution. 2+ or Fe 2+ The content.
[0290] 3. Experimental results.
[0291] As shown in the following table:
[0292]
[0293] 4. Results analysis and conclusion.
[0294] pH value changes: The pH value of the experimental group was relatively stable during the immersion process, indicating that the alkaline environment provided by sodium silicate can effectively buffer pH changes. The pH value of the control group gradually decreased, indicating that there was no effective buffering and protection. Electrochemical impedance changes: The electrochemical impedance value of the experimental group was significantly higher than that of the control group, indicating that the protective layer formed by the synergistic effect of BTA and sodium silicate has higher anti-corrosion performance. The impedance value of the control group decreased significantly due to the lack of chemical passivation of BTA. Metal ion concentration: Cu 2+ The concentration was significantly lower than that of the control group, indicating that the combination of BTA and sodium silicate can effectively reduce corrosion precipitation in metal solutions.
[0295] This experiment verified that benzotriazole (BTA) and sodium silicate work together on the metal surface to form an efficient anti-corrosion protective layer, which significantly improves the metal's anti-corrosion performance. BTA forms a stable chemical passivation layer on the metal surface, and sodium silicate forms a physical protective film on the metal surface. The two complement each other, providing double protection, reducing corrosion reactions, and extending the service life of the metal. This combination can significantly improve the corrosion resistance of equipment in actual industrial applications and is suitable for metal equipment that requires long-term protection in environments such as oil refining and chemical industries.
[0296] Example 9
[0297] This example is used to verify the experimental effect of chitosan and specific enzymes (urease or sulfatase) in improving the deodorization and purification effects.
[0298] 1. Experimental principle.
[0299] Chitosan is a natural adsorbent with strong adsorption capacity. It can adsorb heavy metal ions, oil and organic pollutants in sewage. Specific enzymes (urease or sulfatase) can effectively decompose specific organic pollutants. Urease catalyzes the decomposition of urea into ammonia and carbon dioxide, and sulfatase catalyzes the degradation of sulfate compounds into alcohol and sulfate. The adsorption of chitosan combined with the decomposition ability of enzymes can effectively remove pollutants in sewage and improve the deodorization effect. Enzyme catalyzed reaction:
[0300] Urease catalyzes the decomposition of urea:
[0301]
[0302] Sulfatase catalyzes the breakdown of sulfate esters:
[0303]
[0304] 2. Experimental steps.
[0305] Preparation before the experiment: beaker, measuring cylinder, pipette, magnetic stirrer, pH meter, UV spectrophotometer, bioreactor, chitosan, urease or sulfatase, contamination solution, urine nitrogen test kit, sulfate test kit.
[0306] Experimental steps:
[0307] 1) Solution preparation: Prepare 200 ml of contaminated solution (assuming it contains urea or sulfate compounds) with a concentration of 100 mg / L and pour it into two beakers marked as "experimental group" and "control group" respectively.
[0308] 2) Add reagents:
[0309] Experimental group: 1 g chitosan was added, and 10 units of urease or sulfatase were added respectively.
[0310] Control group: only 1g chitosan was added without adding enzymes.
[0311] 3) Stirring reaction:
[0312] The two beakers were placed on magnetic stirrers respectively and stirred continuously for 30 minutes to ensure that the chitosan was fully in contact with the enzymes.
[0313] Use a pH meter to measure the pH value of the solution regularly and record the data (measure every 5 minutes).
[0314] 4) Sampling and testing:
[0315] Every 10 minutes, take out 5 ml of sample with a pipette and place them into centrifuge tubes marked with time for centrifugal separation (10 minutes).
[0316] The concentrations of urinary nitrogen and sulfate in the solution were measured at each time point using a UV spectrophotometer.
[0317] 5) End point analysis:
[0318] After the 30-minute reaction, the remaining urine nitrogen or sulfate concentration in each group of solutions was measured. The treated solution was further purified through an activated carbon filter. The final purification effect was verified using a urine nitrogen test kit and a sulfate test kit, and the data was recorded.
[0319] 3. Experimental results
[0320] As shown in the following table:
[0321]
[0322] 4. Results analysis and conclusion.
[0323] Changes in urine nitrogen concentration: The decrease in urine nitrogen concentration in the experimental group was significantly greater than that in the control group, indicating that urease plays a significant role in decomposing urea. After 30 minutes, the urine nitrogen concentration in the experimental group dropped to 20 mg / L, while that in the control group was still 50 mg / L.
[0324] Changes in sulfate concentration: The sulfate concentration in the experimental group was significantly reduced, indicating that sulfatase effectively decomposed sulfate compounds. After 30 minutes, the sulfate concentration in the experimental group dropped to 20 mg / L, while that in the control group was still 60 mg / L.
[0325] This experiment verified the combined effect of chitosan and specific enzymes (urease or sulfatase), which showed obvious synergistic effects in pollutant removal and purification. Chitosan adsorbs heavy metal ions and organic pollutants in sewage through its excellent adsorption capacity, forming a porous adsorption layer, providing a good reaction environment for enzyme decomposition. Specific enzymes (urease or sulfatase) effectively decompose organic pollutants, further improving the purification effect and ensuring a low residual concentration of sewage. The combination of the two significantly improved the deodorization and purification effects, met the expectations of the experiment, and provided a practical solution for pollutant removal in actual sewage treatment.
[0326] Example 10
[0327] This example is used to verify the improved effect of the ferrous sulfide passivation deodorant prepared in Example 1 compared with the existing deodorants.
[0328] 1. Experimental principle.
[0329] The ferrous sulfide passivation deodorant prepared in Example 1 contains multiple active ingredients (sodium percarbonate, sodium bicarbonate, DTPA, nonylphenol polyoxyethylene ether, cocamidopropyl betaine, coconut oil alkyl diethanolamide, benzotriazole, chitosan, specific enzymes, sodium silicate and sodium gluconate), which provide a comprehensive solution to the problems of ferrous sulfide spontaneous combustion, odorous gas pollution and equipment corrosion through synergistic effects. The experiment aims to compare the effects of the ferrous sulfide passivation deodorant prepared in Example 1 with existing deodorants in terms of removing iron sulfide, deodorization, corrosion prevention and other properties.
[0330] Passivation and deodorization effect:
[0331] The ferrous sulfide passivation deodorant prepared in Example 1 oxidizes ferrous sulfide through the strong oxidant (hydrogen peroxide) provided by sodium percarbonate, maintains the pH stability of the solution through sodium bicarbonate, DTPA and sodium gluconate chelate metal ions, and cooperates with the active groups formed by nonylphenol polyoxyethylene ether and other surfactants to enhance the deodorization, passivation and cleaning effects.
[0332] Anti-corrosion effect:
[0333] Sodium silicate and benzotriazole form a double protective layer on the metal surface, preventing oxygen and corrosive substances from directly contacting the metal surface and reducing corrosion of the metal surface.
[0334] 2. Experimental steps.
[0335] Preparation before the experiment: beaker, measuring cylinder, pipette, magnetic stirrer, pH meter, UV spectrophotometer, electrochemical workstation, ICP-OES, copper or iron sheet for experiment, jewelry balance, existing deodorant products on the market, artificial sewage for experiment (containing ferrous sulfide and organic pollutants)
[0336] Prepare the solution:
[0337] The ferrous sulfide passivation deodorant prepared in Example 1 was dissolved in 500 ml of deionized water and stirred evenly on a magnetic stirrer.
[0338] Experimental steps:
[0339] 1) Passivation and deodorization performance test:
[0340] Add 500 ml of artificial sewage (containing 1 g / L ferrous sulfide and 500 mg / L organic matter) into two beakers respectively.
[0341] 50 ml of the ferrous sulfide passivation deodorant prepared in Example 1 was added to one beaker, and an equal amount of a commercially available deodorant was added to another beaker.
[0342] The solutions were stirred for 30 min on a magnetic stirrer and the pH change of the solutions was measured using a pH meter.
[0343] Samples (5 ml) were taken every 10 minutes and the concentrations of residual ferrous sulfide and organic matter in the solution were determined using an ultraviolet spectrophotometer.
[0344] 2) Anti-corrosion performance test:
[0345] The copper sheet or iron sheet used in the treatment experiment (as in the previous experiment) was immersed in the ferrous sulfide passivation deodorant solution prepared in Example 1 and the existing commercially available deodorant solution for 5 minutes respectively.
[0346] After drying, place it in a beaker containing 3.5% NaCl solution and let it stand for 24 hours.
[0347] The electrochemical impedance was measured every 2 hours using an electrochemical workstation.
[0348] After 24 hours, the Cu content in the solution was determined by ICP-OES. 2+ / Fe 2+ concentration.
[0349] 3. Experimental results.
[0350] Table 1:
[0351]
[0352] Table 2 (Electrochemical impedance and corrosion ion concentration):
[0353]
[0354] 4. Results analysis and conclusion.
[0355] Passivation and deodorization: After 30 minutes, the residual ferrous sulfide concentration in the experimental group was significantly reduced to 100 mg / L, while that in the control group was 400 mg / L, indicating that the ferrous sulfide passivation deodorant prepared in Example 1 can more effectively oxidize and remove ferrous sulfide. The organic matter concentration in the experimental group also significantly decreased to 50 mg / L, while that in the control group remained at 200 mg / L, indicating that the ferrous sulfide passivation deodorant prepared in Example 1 has a more significant degradation effect on organic matter.
[0356] Anti-corrosion performance: The electrochemical impedance value of the metal samples in the experimental group after immersion for 24 hours was significantly higher than that in the control group, indicating that the ferrous sulfide passivation deodorant prepared in Example 1 formed a more effective protective layer on the metal surface. The ICP-OES measurement results showed that the Cu 2+ The lower concentration further verifies its anti-corrosion efficiency.
[0357] This experiment verifies that the ferrous sulfide passivation deodorant prepared in Example 1 has a significant improvement over existing commercially available deodorants, and exhibits more efficient and longer-lasting performance in removing ferrous sulfide, decomposing organic matter, and preventing metal corrosion.
[0358] The above describes an embodiment of the present invention, but this embodiment is not limited to the above specific implementation methods. The above specific implementation methods are merely illustrative and not restrictive. Under the guidance of this embodiment, ordinary technicians in this field can also make many forms, all of which are protected by this embodiment.
Claims
1. A ferrous sulfide passivation deodorant, characterized in that: The raw materials include the following mass percentages: Sodium percarbonate 0.8%–1.0%, sodium bicarbonate 0.5%–0.7%, diethylenetriaminepentaacetic acid 0.3%–0.4%, nonylphenol polyoxyethylene ether 0.2%–0.3%, cocamidopropyl betaine 0.3%–0.35%, coconut oil alkyl diethanolamide 0.4%–0.5%, benzotriazole 0.1%–0.15%, chitosan 0.1%–0.15%, biocatalyst 0.05%–0.08%, sodium silicate 0.4%–0.6%, sodium gluconate 0.3%–0.5%, and water as the balance.
2. A ferrous sulfide passivation deodorant according to claim 1, characterized in that: The raw materials include the following mass percentages: Sodium percarbonate 0.9%, sodium bicarbonate 0.6%, diethylenetriaminepentaacetic acid 0.35%, nonylphenol polyoxyethylene ether 0.25%, cocoamidopropyl betaine 0.32%, coconut oil alkyl diethanolamide 0.45%, benzotriazole 0.12%, chitosan 0.12%, biocatalyst 0.07%, sodium silicate 0.5%, sodium gluconate 0.4%, balance water.
3. A ferrous sulfide passivation deodorant according to claim 1, characterized in that: The raw materials include the following mass percentages: Sodium percarbonate 0.8%, sodium bicarbonate 0.5%, diethylenetriaminepentaacetic acid 0.3%, nonylphenol polyoxyethylene ether 0.2%, cocoamidopropyl betaine 0.3%, coconut oil alkyl diethanolamide 0.4%, benzotriazole 0.1%, chitosan 0.1%, biocatalyst 0.05%, sodium silicate 0.4%, sodium gluconate 0.3%, balance water.
4. A ferrous sulfide passivation deodorant according to claim 1, characterized in that: The raw materials include the following mass percentages: Sodium percarbonate 1.0%, sodium bicarbonate 0.7%, diethylenetriamine pentaacetic acid 0.4%, nonylphenol polyoxyethylene ether 0.3%, cocoamidopropyl betaine 0.35%, coconut oil alkyl diethanolamide 0.5%, benzotriazole 0.15%, chitosan 0.15%, biocatalyst 0.08%, sodium silicate 0.6%, sodium gluconate 0.5%, balance water.
5. A ferrous sulfide passivation deodorant according to claim 1, characterized in that: The biocatalyst is one or more of urease or sulfatase.
6. A process for preparing the ferrous sulfide passivation deodorant as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1: Preparation and Mixing; Pour water into the mixing container and start the stirring device to ensure uniform mixing of the solution; S2: Add surfactant and corrosion inhibitor; Add nonylphenol polyoxyethylene ether and benzotriazole to the water in the stirring container in sequence, and stir until they are completely dissolved; Then add cocamidopropyl betaine and coconut oil alkyl diethanolamide and continue stirring to ensure complete dissolution and even dispersion; S3: introduction of chelating agents and biocatalysts; Add diethylenetriaminepentaacetic acid and sodium gluconate to the mixture and stir until dissolved; Add chitosan and continue stirring to ensure dissolution and uniform dispersion; Then add the biocatalyst and stir until well mixed; S4: adding passivation and protection components; Add sodium silicate and stir to dissolve, making sure it is evenly mixed; Finally, add the sodium percarbonate and sodium bicarbonate, continuing to stir to ensure that all ingredients are fully dissolved and evenly distributed; S5: end stirring; Keep stirring to ensure all ingredients are fully dissolved and evenly mixed; S6: Packaging and storage; The prepared ferrous sulfide passivation deodorant solution is filtered to remove undissolved particles, and the filtered solution is placed in a suitable plastic or stainless steel container and sealed for storage, avoiding direct sunlight.
7. The preparation process of a ferrous sulfide passivation deodorant according to claim 6, characterized in that: In step S2, nonylphenol polyoxyethylene ether and benzotriazole are added to the water in the stirring container in sequence, with the stirring time being 30-60 minutes and the stirring temperature being 25-40° C., and the stirring is carried out until the water is completely dissolved.
8. The preparation process of a ferrous sulfide passivation deodorant according to claim 6, characterized in that: In step S3, diethylenetriaminepentaacetic acid and sodium gluconate are added to the mixed solution, stirred for 30-60 min at a temperature of 25-35° C., and stirred until completely dissolved.
9. The preparation process of a ferrous sulfide passivation deodorant according to claim 6, characterized in that: In step S4, sodium silicate is added, the stirring time is 30-50 minutes, the stirring temperature is 25-30°C, and after stirring and dissolving, ensure uniform mixing.
10. The preparation process of a ferrous sulfide passivation deodorant according to claim 6, characterized in that: In step S5, the stirring time is 3-10 min, and the stirring temperature is 25-35°C.
Citation Information
Patent Citations
Ferrous sulfide passivation cleaning agent and preparation method and application thereof
CN102912366A
Integrated in-situ remediation and treatment medicament of surface black and odorous water and bottom mud as well as preparation method and application thereof
CN107555498A
Composite deodorizing passivator and preparation method thereof
CN112281168A
Ferrous sulfide passivation deodorant and preparation method thereof
CN117866658A